Diversity of Phytoplankton in Seagrass Beds at Ko Yao Yai, Phangnga Province - เจริญวัฒนาพร จิรพร (KKU Science Journal, 2012)
A Phytoplankton community survey was carried out in the seagrass beds of Ao Lo Pa Lai and Ao Lo Po Yai, Ko Yao Yai, Phangnga Province. Sampling was conducted in January and July 2005. Water samples were filtered through a nylon net with mesh size 20 micrometers. A total of 4 classes with 57 genera were identified as Cyanophyceae (4 genera), Bacillariophyceae (39 genera), Dinophyceae (13 genera) and Dictyochophyceae (1 genera). The dominant genera consisted of Cylindrotheca, Nitzschia, Pleurosigma, Pseudo-nitzschia, Paralia, Chaetoceros and Thalassiosira. Diatom was the dominant group from both study areas. Cylindrotheca and Nitzschia were found in high abundance at Ao Lopoyai. Species diversity index, similarity index and richness index ranged between 0.89 – 1.39, 0.56 – 0.91 and 2.51 – 4.94, respectively. The relationships between environmental factors and phytoplankton abundance demonstrated that the phytoplankton abundance negatively correlated with pH and positively correlated with chlorophyll a concentrations.